Everyday Catholicism : seeing God's action in our lives - Thieman, LeAnn (Chicken soup for the soul, 2020)
These compelling stories present convincing evidence of God's active presence in our everyday lives. Whether you're a cradle Catholic or a convert, solid in the Faith or wavering, these stories will deepen your conviction and stimulate your hope and trust in God. This extensive selection of faith-strengthening stories includes those of... *Joan, who recited Hail Marys on her Buddhist, 108-bead strand while standing at her dying father's bedside and is transformed when she receives a glimmering rosary from beyond the grave. ("The White Rosary") *Jennifer, who, while walking in a strange place and having no idea (yet!) that she needed protection, is suddenly accompanied by a large, friendly, vigilant dog. ("Four-Legged Angel") *Sharon, who, distraught over having misplaced a precious jewelry box, rejoices at the effect that finding the box has on her teenage son's faith. ("Lost and Found") Blair, an exhausted, overworked hospital resident who orders the wrong test on a patient a Catholic priest and whose encounter with him afterward is both startling and everlasting. ("The Accident") *Donna, a patient who had derived valuable assistance and deep comfort from regular phone consultations with a nurse and who calls one last time to say thank you and is amazed by what she learns. ("Angel on the Line") *Angela, whose East Texas Sunday school class decided to pray for snow and whose students at the boys' prison where she volunteers discover the remarkable power of prayer. ("Please, God, Make It Snow") Your faith will be bolstered and your heart leavened by these poignant, true-life accounts of God's grace in action and how it invigorates and transforms people's lives.